Succession rights of foreign citizens in the Republic of Uzbekistan - Nadirbekova Umida Karamatdin qizi; Bayjanova Ramuza Teǹelbay qizi (Zien Journals, 2022)
In this article, the inheritance rights of foreign citizens and stateless persons, their practice and problems in the field of legal regulation, and the reforms during the period of independence are highlighted
Keywords: foreign; stateless; inheritance; property